2012
DOI: 10.1124/mol.112.078873
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotics and Loss of Cell Adhesion Drive Distinct Transcriptional Outcomes by Aryl Hydrocarbon Receptor Signaling

Abstract: The aryl hydrocarbon receptor (AhR) is a signal-regulated transcription factor, which is canonically activated by the direct binding of xenobiotics. In addition, switching cells from adherent to suspension culture also activates the AhR, representing a nonxenobiotic, physiological activation of AhR signaling. Here, we show that the AhR is recruited to target gene enhancers in both ligand [isopropyl-2-(1,3-dithietane-2-ylidene)-2-[N-(4-methylthiazol-2-yl)carbamoyl]acetate (YH439)]-treated and suspension cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…Promoter activity of a purified XRE is identified in cells cultured in collagen matrices, consistent with previous findings that increased activation of the XRE signals occurs in cells suspended in semisolid media containing 1.68% methylcellulose (Sadek and Allen-Hoffmann 1994, Hao et al 2012) or cultures within ultralow attachment plates (Sengupta et al 2014). Despite the decrease in XRE activity in HD matrices, the expression of CYP1B1 and CYP4B1, which are regulated in part by XRE elements, are significantly increased in HD matrices.…”
Section: Discussionsupporting
confidence: 89%
“…Promoter activity of a purified XRE is identified in cells cultured in collagen matrices, consistent with previous findings that increased activation of the XRE signals occurs in cells suspended in semisolid media containing 1.68% methylcellulose (Sadek and Allen-Hoffmann 1994, Hao et al 2012) or cultures within ultralow attachment plates (Sengupta et al 2014). Despite the decrease in XRE activity in HD matrices, the expression of CYP1B1 and CYP4B1, which are regulated in part by XRE elements, are significantly increased in HD matrices.…”
Section: Discussionsupporting
confidence: 89%
“…Little is known about the AHR-dependent regulation of the TiPARP upstream regulatory region. The isolated mouse TiPARP promoter was unresponsive to TCDD, which might be due to its high constitutive expression levels [21]. These findings might also suggest a more complex mechanism of regulation of TiPARP .…”
Section: Resultsmentioning
confidence: 99%
“…The AHR-ARNT heterodimer binds to dioxin response elements (DREs) in the promoter region of downstream target genes and directly upregulates their expression [38]. Activated AHR is also capable of downregulating expression, and multiple studies have reported a larger number of genes being downregulated rather than upregulated following AHR activation [41,42,43,44,45,46,47]. However, it is less clear whether transcriptional downregulation is the result of AHR binding directly to the promoter, or if it is an indirect effect due to (1) AHR-induced upregulation of transcriptional inhibitors or (2) AHR-induced degradation of other transcriptional activators (discussed below).…”
Section: Ahr Signalingmentioning
confidence: 99%